Strategi Adaptif Dalam Meredakan Konflik Keluarga - Tendean, Jolf John; Sinaga, Janes; Nainggolan, Sarwedy; Sinambela, Juita Lusiana (PT. PENERBIT TIGA MUTIARA, 2023)
This study aims to analyze the role of adaptive strategies in reducing conflict in the family environment. Through a qualitative approach with case studies, researchers investigate how families deal with and overcome conflict responsively and flexibly. These findings indicate that adaptive strategies, such as effective communication, healthy emotional management, respect for differences, and negotiation skills, have a crucial role in reducing family conflict. This strategy not only contributes to conflict resolution, but also to growth and emotional closeness among family members. The implications of this research provide insight into how families can address conflict challenges in a constructive way, promote harmonious relationships, and support collective growth.